Entrepreneurship education challenges for green transformation - T\~onis Mets; Jack Holbrook; Siim Läänelaid (Administrative Sciences, 2021)
Associated with global climate agreements and the European Union's focus on climate-neutral goals by 2050, the development of Green Transformation competencies in society has become topical. This viewpoint paper proposes a conceptual model for applying Entrepreneurship Education (EE) to designing an integrated transdisciplinary, Green Transformation Competence framework. In line with this, EE is seen as a tool for developing an active, informed, responsible, yet sustainable, living ecosystem-oriented and green orientation of citizens in the education system. Nevertheless, this viewpoint recognises several challenges for further research.
Keywords: 350; competence framework; conceptual model; entrepreneurship education; green transformation; multidisciplinary; sustainability; transdisciplinary